Preventive Effects of Spirulina platensis on Exercise-Induced Muscle Damage, Oxidative Stress and Inflammation in Taekwondo Athletes: A Randomized Cross-Over Trial - Arvin Kashani; Seyed Ali Keshavarz; Hamed Jafari-Vayghan; Kamal Azam; Mohammad Hozoori; Mina Alinavaz; Kurosh Djafarian (Tabriz University of Medical Sciences, 2022)
Background: Spirulina is an interesting nutritional supplement that has attracted a lot of attention. The aim of the present study was to examine the effect of spirulina supplementation on oxidative stress, inflammatory factors and plasma markers of exercise-induced muscle damage in male taekwondo athletes. Methods: A total of 18 trained taekwondo male athletes took part in a double-blind, placebo-controlled crossover study. Each subject received either spirulina (8 g/day) or placebo for 3 weeks. The study had two periods separated by a 14-day washout. Blood samples were taken after finishing a training checklist program (4 times in total). Results: There were no significant carryover effects; therefore, the two-week washout period was adequate. Compared to the placebo, a dose of 8 g / d of spirulina supplement over 21 days resulted in a significant decrease in plasma levels of lactate dehydrogenase (LDH), creatine kinase (CK) and interleukin 6 (IL6) and a significant increase in plasma levels of total antioxidant capacity (TAC), superoxide dismutase (SOD) and glutathione peroxidase (GPX) (p<0.05). There was not any statistically significant change in the plasma malondialdehyde (MDA) (p>0.05). Conclusion: Due to the improvement of antioxidant and anti-inflammatory conditions as well as appropriate protein content, spirulina supplementation can produce a preventive effect on exercise-induced muscle damage in taekwondo athletes.